2023
DOI: 10.1002/ange.202218491
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Trichromatic Upconversion with High Color Purity in Core‐Shell Nanoparticles for a Full‐Color Display

Abstract: Materials with tunable emission colors has attracted increasing interest in both fundamental research and applications. As a key member of light‐emitting materials family, lanthanide doped upconversion nanoparticles (UCNPs) have been intensively demonstrated to emit light in any color upon near‐infrared excitation. However, realizing the trichromatic emission in UCNPs with a fixed composition remains a great challenge. Here, without excitation pulsed modulation and three different near‐infrared pumping, we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
(80 reference statements)
0
1
0
1
Order By: Relevance
“…Guo et al reported that the pure green, red and blue emissions are obtained in Yb 3+ /Ln 3+ (Ln = Er, Ho, Tm) co-doped Gd 2 O 3 up-conversion phosphors by adjusting the doping concentration of Er 3+ , Ho 3+ and Tm 3+ , which is attributed to the strengthened cross relaxation processes 14 . To obtain broader range emission colors, the core–shell structured nano-materials are rational design in the past few years 11 , 18 22 . Jang et al reported that the emission colors from heavily doped NaErF 4 :Tm-based core@ multi-shell nano-materials were fine tuned through changing the excitation laser from 980 to 808 and 1550 nm and the full-color emissions, including green, red and blue, were achieved via combination effects of elemental migration and photon blocking 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al reported that the pure green, red and blue emissions are obtained in Yb 3+ /Ln 3+ (Ln = Er, Ho, Tm) co-doped Gd 2 O 3 up-conversion phosphors by adjusting the doping concentration of Er 3+ , Ho 3+ and Tm 3+ , which is attributed to the strengthened cross relaxation processes 14 . To obtain broader range emission colors, the core–shell structured nano-materials are rational design in the past few years 11 , 18 22 . Jang et al reported that the emission colors from heavily doped NaErF 4 :Tm-based core@ multi-shell nano-materials were fine tuned through changing the excitation laser from 980 to 808 and 1550 nm and the full-color emissions, including green, red and blue, were achieved via combination effects of elemental migration and photon blocking 19 .…”
Section: Introductionmentioning
confidence: 99%
“…光区到紫外光区的广泛发射(如图 1 所示) [6][7][8] 。不仅如 此,与有机染料相比,镧系元素的发射谱线更加尖 锐,从而赋予了它们极高的色光纯度。此外,这些镧 系掺杂的上转换发光材料还具备出色的抗光漂白性 能、超大的 Stokes 位移以及良好的生物相容性等特 点。这些优势是有机染料、量子点等其他发光材料所 无法比拟的 [9][10][11][12][13][14] 。 稀土离子的能级结构通常呈现阶梯状排列,其激 发态具有较长的寿命,这一特性使得它们成为制备上 转换发光材料的理想选择。早在 1959 年,物理学家 Bloembergen [15] 就提出了上转换发光的概念,即通过 低能量光子的激发获得高能量光子的发射,从而实现 反 Stokes 发光。近年来,随着纳米科学和纳米技术的 迅猛进步,稀土上转换材料已经历了从较大尺度到纳 米尺度的演变。在纳米尺度上的精细调控进一步丰富 了上转换材料的功能性,使其在生物医学 [16][17][18][19][20][21] 、光学 传感 [22][23][24][25][26][27][28][29][30][31][32][33][34][35] 、显示器件 [36][37][38][39][40][41] 等领域的应用日益凸显。例 如,利用稀土上转换发光材料发光波长可调的特性, 可以实现多种生物分子的同时成像。此外,通过将药 物与稀土上转换发光材料结合,借助外部激发,便可 控制药物的释放,进而达到精准治疗的目的。 上转换发光是一种特殊的发光现象,它没有遵守 斯托克斯位移规律,即吸收低能量的光子却能发射出 较高能量的光子,两者之间的能量差被称为斯托克斯 位移 [42][43] 。典型的上转换材料通常由三部分构成:基 质、敏化剂和激活剂。基质虽然不直接参与发光过 程,但它为敏化剂和激活剂提供了一个稳定的晶格环 境,并且对效果产生着重要影响。不同的晶体结构会 导致发光的差异性。常见的基质材料包括氧化物、氟 化物和硫化物等,其中氟化物具有较低的声子能量因 图 1 在硅酸盐玻璃中观察到的具有主要可见发射跃迁的三价稀土离子的能级图,用箭头表示荧光的近似颜色。横过图的水平线表示用波 长(nm)标记的常见有机标签激发源的位置。用 365 nm 谱线激发稀土离子 [6] Figure 1 Energy level diagram of trivalent RE ions with dominant visible emission transitions observed in silicate glasses designated by arrows representing the approximate color of the fluorescence. Horizontal lines extending across the diagram designate the location of common organic label excitation sources labeled by wavele...…”
unclassified